Impact of occupation on survival of esophageal squamous cell carcinoma patients following esophagectomy: a long-term survival analysis - Kexun Li; Simiao Lu; Jie Mao; Huan Zhang; Kangning Wang; Guangyuan Liu; Qifeng Wang; Yongtao Han; Lin Peng; Xuefeng Leng (BMC Gastroenterology)
Abstract Background Esophageal cancer (EC), particularly esophageal squamous cell carcinoma (ESCC), is a major global health issue with high incidence and mortality rates in Asia. This study examines the impact of occupational background on the long-term survival of ESCC patients following esophagectomy. Methods Data were obtained from the Sichuan Cancer Hospital & Institute Esophageal Cancer Case Management Database (SCCH-ECCM Database), focusing on patients with ESCC who underwent esophagectomy between 2010 and 2017. Patients were classified into four occupational groups: Farmer, Civil Servant, Teacher, and Factory Worker. The primary outcome measured was overall survival (OS), which was analyzed using Kaplan–Meier survival curves, Cox proportional hazards models, and restricted mean survival time (RMST). To account for potential confounding factors, propensity score matching (PSM) was employed. Results Among the cohort, 67.5% were Farmers, 9.0% Civil Servants, 1.9% Teachers, and 21.6% Factory Workers. The median follow-up was 72.2 months, with a median OS of 49.8 months. One-, three-, and five-year OS rates varied slightly by occupation, with Factory Workers displaying the highest one-year survival rate at 91%. Significant survival differences were noted between Farmers and Civil Servants (HR: 1.291; 95% CI: 1.030 − 1.618; P = 0.027),the significance persisted even after PSM (HR: 1.376; 95% CI: 1.004 − 1.885; P = 0.047). Civil Servants, who presented with more advanced disease stages, had the lowest crude RMST, aligning more closely with other groups after adjustment. Conclusions The results revealed that ESCC patients categorized as Civil Servants exhibited a poorer prognosis compared to those classified as Farmers.